Brave new Bollywood : in conversation with contemporary Hindi filmmakers - Nirmal Kumar, 1964-; Chaturvedi, Preeti (SAGE Publications, 2015)
This book examines filmmakers in India, their religious beliefs, social moorings, cinematic influences, attitudes towards filmmaking and experiences of making movies.--Publisher's description.